Socio-Emotional Characteristics in Early Childhood and Offending Behaviour in Adolescence - Garcia, Paul (International Journal of Population Data Science, 2025)
Objectives This paper explores the relationship between child development and the probability of engaging in offending behaviour during adolescence. It also investigates the pathways through which early developmental traits may influence the probability of engaging in offending behaviour as individuals transition into adulthood. Methods I perform a factor analysis to identify underlying patterns in early childhood assessments. These factors are then used to predict the likelihood of offending during adolescence. Mediation analysis is employed to explore how socio-emotional factors may indirectly affect adolescent offending through mediators such as educational performance and school-related issues. Finally, multi-level modelling is used to examine how socio-emotional development and contextual factors such as school characteristics interact to influence offending behaviour, accounting for group-level variability. Results and Conclusions The factor analysis reveals several key developmental dimensions. After controlling for confounding variables, significant associations are found between poor child development and adolescent offending. Cognitive development issues are primarily mediated by school-related experiences like attendance and academic performance. In contrast, socio-emotional challenges continue to show a strong association with offending behaviour, even when these mediating factors are considered. Results remain robust even after accounting for group-level variability.